Variation among populations of Galapagos land iguanas (Conolophus): contrasts of phylogeny and ecology. - Snell, H. L., Snell, H. M., Tracy, C. R. (1984)
See: Berry, R. J. ed. Evolution in the Galapagos Islands, Academic Press, London, UK. 576.8 BER BIB Now: 6485
English
Keywords: LI, EV, EC -- Variation among populations of Galapagos land iguanas (Conolophus): contrasts of phylogeny and ecology